Pengaruh Beban Kerja dan Tingkat Stres Terhadap Kinerja Guru pada SMP N 1 SEI Rampah - Beny Arianata Sidabutar; Sastro Gunadi Sianturi; Rusmewahni Mahwiarja; Cia Cai Cen (MES Management Journal, 2025)
This research was conducted with the aim of determining the effect of workload and stress levels on teacher performance at SMP N 1 Sei Rampah. The number of respondents in this study was 34 people. In this research, the sampling technique used was Total Sampling. The type of research employed is quantitative research, which is based on positivist philosophy and used to study a specific population or sample. Data collection utilized research instruments, and data analysis was quantitative/statistical, aiming to test the established hypotheses. The data analysis tool used in this study was SPSS (Statistical Package for the Social Sciences). The results of the study indicate that: workload does not affect teacher performance at SMP N 1 Sei Rampah. Work stress does not affect teacher performance at SMP N 1 Sei Rampah. Workload and work stress do not have an effect. Jointly (simultaneously) against the Teacher Performance at SMP N 1 Sei Rampah.